Spatial Accessibility for Campus Public Spaces: A Space Syntax Study of Universitas Nusa Cendana - Cintya Tualaka, Theodora Murni; Wiras Hardy, I Gusti Ngurah; Dahoklory, Lodwik O. (West Science Interdisciplinary Studies, 2025)
Public open spaces (POPs) within the campus environment play a crucial role in supporting the psychological well-being, social interaction, and quality of life of the academic community. This study aims to evaluate the spatial accessibility of POPs within the Nusa Cendana University (Undana) campus using a space syntax approach. By combining Axial Map analysis and user perception surveys, this study assesses the spatial connectivity, integration (HH), and intelligibility of three vacant plots of land with the potential to be developed as POPs. The analysis results indicate that plot B has the highest integration value (0.48) and a gentle contour, making it the most feasible location spatially and topographically. The regression test results indicate that perceived accessibility has a positive and significant effect on the assessment of public space feasibility (r = 0.582, p < 0.01), in line with the theories of Lynch (1960) and Jacobs (1961) regarding the role of accessibility and visibility in shaping functional public spaces. This study confirms that the space syntax approach combined with user perception can be an evidence-based evaluation instrument in planning more inclusive and adaptive campus public spaces.